2018
DOI: 10.18535/ijmsci/v5i3.06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Red Blood Cell Distribution Width (RDW) and Neutrophil Lymphocyte Ratio (NLR) in Diagnosis of Appendicitis in Paediatric Patients in H. Adam Malik Medan Central General Hospital

Abstract: Acute appendicitis in paediatric patient is among the causal of abdominal emergency which requires immediate operation (Victor, et al, 2012; Ballester et al., 2009; Huckins et al., 2013). The incidence of acute appendicitis in paediatric patient in the world ranges from 1 to 8 % of all pediatric patients coming to the Emergency Department (ED) with acute abdominal pain (Jangra et al., 2013). Appendicitis is rare in children under 5 years, and very rare in the first year of life. In some instances, boys are mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
1
1
0
2
Order By: Relevance
“…In our study, the NLR was not a useful laboratory parameter for discriminating cases of simple AA from cases of complicated AA, given its poor discriminatory power (AUC < 0.7). The results obtained in this study are similar to those reported by Kelly et al, 10 Paramita et al, 29 and Kostakis et al 8 Our results suggest that the NLR cannot be used as a parameter to confirm or rule out the presence of AA. However, it can be used in conjunction with other tests, symptoms, and clinical signs to select patients in whom further tests are required.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, the NLR was not a useful laboratory parameter for discriminating cases of simple AA from cases of complicated AA, given its poor discriminatory power (AUC < 0.7). The results obtained in this study are similar to those reported by Kelly et al, 10 Paramita et al, 29 and Kostakis et al 8 Our results suggest that the NLR cannot be used as a parameter to confirm or rule out the presence of AA. However, it can be used in conjunction with other tests, symptoms, and clinical signs to select patients in whom further tests are required.…”
Section: Discussionsupporting
confidence: 89%
“…28 In studies that assessed the usefulness of the NLR in the diagnosis of AA in children, the reported prevalence of complicated appendicitis ranges from 11% to 68%. 10,29 In this study, the pediatric surgeon was responsible for determining the need for surgery for suspected AA, after a clinical and analytical assessment. Since misdiagnosed appendicitis can have serious complications and even lead to death, the objective of diagnostic testing is to avoid false negatives.…”
Section: Discussionmentioning
confidence: 99%
“…28 En los estudios que evalúan la utilidad del INL en el diagnóstico de AA en niños, la prevalencia de apendicitis complicada reportada es del 11 % al 68 %. 10,29 En este estudio, el cirujano pediatra fue el que determinó la necesidad de cirugía por la sospecha de AA, tras una evaluación clínica y analítica. Dado que la apendicitis mal diagnosticada puede tener complicaciones graves e incluso provocar la muerte, el objetivo de las pruebas diagnósticas es evitar los falsos negativos.…”
Section: Discussionunclassified
“…En nuestro estudio, el INL no fue un parámetro de laboratorio útil para discriminar los casos de AA simple de los casos de AA complicada, dada su pobre capacidad de discriminación (ABC < 0,7). Los resultados obtenidos en este estudio son similares a lo reportado por Kelly et al, 10 Paramita et al 29 y Kostakis et al 8 Nuestros resultados sugieren que el INL no puede usarse como un parámetro para confirmar o descartar la presencia de AA. No obstante, puede emplearse junto con otras pruebas, síntomas y signos clínicos para seleccionar a los pacientes en los cuales es necesario un mayor estudio.…”
Section: Discussionunclassified